Analisa Perpindahan Panas Paving Block Terbuat dari Abu Boiler Sisa Pembakaran Serat dan Cangkang Kelapa Sawit - St Nugroho Kristono (Politeknik Kelapa Sawit Citra Widya Edukasi, 2017)
Paving block of boiler ash is a building material product made from residual burning of fiber and palm shells in boiler, as well as manually stirred cement and then printed. Paving block is used as cover or hardening of soil surface that can absorb water. There is standardization of paving block strength. The purpose of this research is to know the amount of heat transfer that occurs in paving block made from burning residue in boiler at palm oil mill and heat transfer in ordinary paving block. There are 4 different compositions between boiler ash and cement in the manufacture of the paving block, ie: 1:1; 1:3/4; 1:1/2; and 1:1/4. The density of paving block from boiler ash is 1,175.26 Kg/m³, while the typical paving block weight is 2,110.10 Kg/m³. The thermal conductivity of the paving block is 0.72 W/m.K. Different heat transfer values ​​are obtained between paving block of boiler ash with regular paving blocks. For paving block of boiler ash with composition 1:1; 1:3/4; 1:1/2; and 1:1/4 with hot temperature (Tp) 200⁰C and cold temperature (Td) 32⁰C obtained heat transfer value (q) of 48.98 W. While the usual paving block with temperature 200⁰C and cold temperature (Td) 33⁰C obtained heat transfer value (q) of 37.36 W. Maximum test temperature of 200⁰C does not change the structure and dimensions of the paving block of boiler ash.